The questions raised by the absences and emergencies of Boaventura de Sousa Santos - Marcos, Jairo (2025)
Deepening in the borders from where Boaventura de Sousa Santos lives and thinks. Critical description of his responsibility for the victims, from the recognition of the other plural as an equal, whenever the difference detracts him or her, and as different, whenever the equality threats her or his identity.